1992
DOI: 10.1159/000462193
|View full text |Cite
|
Sign up to set email alerts
|

A Hemolytic Reaction Implicating Sd^a Antibody Missed by Immediate Spin Crossmatch

Abstract: Anti-Sd^a, an antibody not usually considered to cause of hemolytic transfusion reactions, possibly was related to hemolysis following transfusion of red blood cells expressing strong Sd^a antigen. Prior to transfusion, the antiglobulin antibody screen performed in LISS and an immediate spin crossmatch were negative. Retrospectively, after hemolysis was detected, an antiglobulin crossmatch with red cells from the transfused unit revealed microscopic incompatibility. The transfused unit proved to have strong ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Due to the generally low expression of SDa on RBC in most individuals, the rarity of CAD individuals and the low level and low‐temperature reactivity of anti‐SDa IgM, the SDa antigen, and antibody do not create a significant transfusion risk. Rare hemolytic reactions have been reported, however, in association with RBCs with high levels of SDa expression . This suggests that porcine ECs and organs expressing SDa (discussed below) may be at risk of early antibody‐mediated immune injury.…”
Section: The Sda Human Blood Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the generally low expression of SDa on RBC in most individuals, the rarity of CAD individuals and the low level and low‐temperature reactivity of anti‐SDa IgM, the SDa antigen, and antibody do not create a significant transfusion risk. Rare hemolytic reactions have been reported, however, in association with RBCs with high levels of SDa expression . This suggests that porcine ECs and organs expressing SDa (discussed below) may be at risk of early antibody‐mediated immune injury.…”
Section: The Sda Human Blood Groupmentioning
confidence: 99%
“…Clear evidence supporting the classification of SDa as a high-frequency polyagglutinable antigen 28 SDa expression. 32,33 This suggests that porcine ECs and organs expressing SDa (discussed below) may be at risk of early antibodymediated immune injury.…”
Section: The S Da H Uman B Lood G Roupmentioning
confidence: 99%
“…There are a considerable number of reports of hemolytic transfusion reactions caused by antibodies that were not detected by antibody screen or by IS-XM, but that would have been detected by IAT-XM. [5][6][7][8] Even though those antibodies mainly are cold-reactive or are against low-incidence antigens, the odds of encountering them increase in patients who are immunologic responders and consequently prone to RBC alloimmunization. 9 Indeed, the decision to eliminate IAT-XM is associated with a risk of hemolytic transfusion reactions of 1:2000 transfused units, 10 which is a significant value, especially in large transfusion laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Most survival studies with 51 Cr -labelled cells in patients with anti -Sd a have shown insignifi cant reduction in red cell survival, even when Sd(a ++ ) cells were used [24,25] . A couple of HTRs, allegedly caused by transfusion of Sd(a ++ ) cells to a patient with IgM anti -Sd a , are reported [24,25] .…”
Section: Anti-sd Amentioning
confidence: 99%